PDIP Political Dynasty Phenomenon Ahead of The 2024 Election - Devina Indah Harini (Wadah Inovasi Indonesia, 2023)
This study's main objective is to examine the issue of identity politics and political dynasties in Indonesia, with Solo serving as a case study of these issues in relation to the simultaneous general elections for the head of state and president in 2024. Political dynasties that surround power conflicts at the local to national levels are closely related to the functioning of political parties and the rules governing local elections. Political dynasties continue to create powerful networks of influence to dominate political parties and put an end to democracy. In order to have concurrent head of state or presidential elections in 2024, this study tries to explain the phenomena of identity politics and political dynasties. This study employs a descriptive research design and a qualitative methodology. Data were gathered from literature reviews by examining other studies that were conducted on the same subject as well as news articles in the media regarding the subject of identity politics and political dynasties. According to the study's findings, identity politics and political dynasties still exist in Solo and have a high likelihood of resurfacing during the 2024 presidential election. Additionally, issues with hate speech, anti-black campaigns, and hoaxes have also surfaced using various models, particularly through social media and billboards.